(untitled) (Scientia Agropecuaria, 2026)
Camu camu is an Amazonian fruit shrub from the Myrtaceae family, naturally growing in floodplains of the Amazon basin. Its significance lies in its fruit production, characterized by high vitamin C content and bioactive components. This study aimed to identify promising accessions within the camu camu germplasm collection in the Peruvian Amazon by evaluating multiple morphological traits and high phenotypic stability across different cropping seasons. A panel of 215 individuals from 43 accessions was evaluated over three growing seasons (2021/2022, 2022/2023, and 2023/2024) to identify stable accessions. Twenty-six quantitative descriptors were analyzed, including traits related to leaves, flowers, fruits, seeds, and fruit yield per plant. The Weighted Average of Absolute Scores Biplot (WAASB), based on the Best Linear Unbiased Predictions (BLUPs) of the genotype-environment interaction, was employed to assess the stability of accessions across three growing seasons. Factor analysis was also used to identify relationships among multiple variables. The genotype x environment interaction (GEI) effects were significant for all descriptors, except for ºBrix, while environmental effects were significant for most descriptors. A cumulative variance of 74% was explained by eight principal components. The BLUP analysis and WAASB index effectively identified stable camu camu accessions with high agromorphological values, emphasizing their contribution to the genetic variability of the collection. Furthermore, the MET evaluation facilitated the selection of accessions with multiple traits adapted to diverse environments. Results highlight the efficiency of BLUP and WAASB in assessing genotypic stability, resource optimization, and sustainability in breeding programs for this species.